Two Projects - Brad Cloepfil (Oz, 2001)
Sitings: Five Reflections on Architectural Domain, 1994–present Premise The eroding quality of our built and unbuilt landscape has become a familiar topic of the popular media as well as a concern of architects, planners and other critics of contemporary culture.